Cornstarch nanocrystals as a potential fat replacer in reduced fat O/W emulsions: A rheological and physical study. (May 2019) - Javidi, Fatemeh; Razavi, Seyed M.A.; Mohammad Amini, Asad
Abstract: The objective of this study was to evaluate cornstarch nanocrystals (CSNC) suspensions (10, 12 and 14%) as a fat replacer in reduced fat emulsions (25% fat reduced: 25FR, 50% fat reduced: 50FR and 75%fat reduced: 75FR). Atomic force microscopy (AFM) showed rounded edge platelet-like particles with size around 10–150 nm. Sulfate content and zeta potential of CSNC were 0.21% and −34.6 mV, respectively. Nanocrystals crystallinity (36.8%) was higher than the source starch (25.7%). Rheological and physical properties of reduced fat emulsions were compared to full-fat emulsion (control, 80% fat). All the emulsions indicated good homogeneity (PDI = 0.21–0.29). There was no significant difference between the Z-average of the control and some samples (25FR with 14% CSNC, 50FR with 12% CSNC and 75FR with 10–12% CSNC). The reduced fat emulsions showed higher absolute zeta potential values (33.2–39.4 mV) than control (31.9 mV), resulting from the negatively charged surface of CSNC. Although the full-fat emulsion revealed the highest whiteness index (99.27), no significant changes were observed at the low levels of fat reduction and CSNC substitution. On the basis of dynamic rheological properties, the emulsions indicated a more solid like behavior as a result of fat reduction and CSNC addition, related to smaller droplet size and more negative charges. The reduced fat samples had more spreadability than the control. The results indicated a probable formation of nanocrystal network in the continuous phase, which trapped the oil droplets and prevented creaming after 6-month storage. Graphical abstract: Image 1 Highlights: Reducing fat and adding CSNC led to smaller droplet size and more zeta potential. The ability of CSNC to strengthen the structure was affirmed by rheological data. All reduced fat emulsions showed more solid-like behavior than full fat sample. No creaming was observed for all studied emulsions after 6-month storage. Higher spreadability was obtained as fat reduction and CSNC levels increased.